Pelatihan Pengajaran Bahasa Inggris Berbasis Pendekatan Saintifik - Resty Wahyuni; Alfitriani Siregar; Rita Harisma (Abdimas Universal, 2023)
This community services aimed to provide the training of teaching early childhood for teachers in using English based on a scientific approach in Medan. The method used is based on an analysis of the needs of English-speaking teachers in the city of Medan. This training carried out in three stages, namely preparation, implementation, and evaluation. The result of this training is to train teachers' teaching skills using educative learning tools in schools by practicing English vocabulary which is easier based on a scientific approach, namely observing, asking questions, gathering information, reasoning, and communicating. And enthusiastic teachers for  teaching using beginner’s English can provide new vocabularies and improve language development to children.